Effect of the Synthesis Time on Structural Properties of Copper Oxide - alsoltani, karrar; H. Harbbi, Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The structural properties of the CuO nanopowder oxide prepared reflux techniquewithout any templates or surfactant, using copper nitrate hydrate (Cu(NO)3 3H2O) in deionizedwater with aqueous ammonia solution are reported. The Xrd analysis data and processing in originpro program used to get FWHM and integral width to study the effect of different synthesis timeswas studied on the structural properties. It was found that values of crystal sizes are 17.274nm,17.746nm, and 18.560nm, the size of nanoparticles is determined by Halder-Wagner, and 15.796nm, 15.851nm, and 16.52nm, were calculated by Size-Strain Plot (SSP) method. The Sample wasconsidered to determine physical and microstructural parameters such as internal strain,dislocations density, surface area, and the number of unit cells and then to compare the results.